Internet addiction in late adolescence: profile and patterns of use - George Nunes Bueno (2024)
Introduction: Cross-sectional school-based epidemiological survey, conducted in 2016 and 2017, from a representative sample of 15 to 19-year-old students enrolled in the Greater Vitória Metropolitan Region (RMGV-ES), Espírito Santo, Brazil. Objectives: To verify the association between Internet Addiction, sociodemographic characteristics and the pattern of Internet and social media use. Methods: Cross-sectional study with 2293 students. The sociodemographic data of the individuals and information on internet and social media dependence were verified using the Internet Addiction Test (IAT). Frequencies were calculated and Chi-square and Binomial Logistic Regression tests were applied. Results: Internet addiction was associated with adolescents in the early years (p = 0.001), those with less-educated household heads (p = 0.018), and those who spent four or more hours a day surfing the internet (p < 0.001) and those who used the Internet every day of the week (p = 0.004). Internet addiction was also associated with the use of Twitter (p-value = 0.040), subjective reasons for use (p = 0.001) and those who stopped using it for social reasons (p = 0.001). Conclusion: Public policies that envision the education of adolescents and their families, as well as protection focused on the most susceptible individuals, should be developed. Therefore, it is necessary to prevent adolescents from having daily access to the Internet, not exceeding four hours of use, in order to reduce the risk of dependence and protect the individual from this situation.